2009
DOI: 10.1039/b813562b
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance spectroscopy in analysis of UO2 scale: derivation of a kinetic model of uranium oxidation

Abstract: In this study, we analyzed the development of a compact oxide scale built in course of Uranium surface oxidation. The process was monitored by an in-situ acquisition of the reflectance interference peaks in the NIR-MIR. Dielectric properties of the growing oxide scale were derived in accord to the oscillator model. We used effective media approach to simulate heterogeneous dielectric content in the oxide-metal interface. Following dielectric parameterization, structural properties (e.g., scale thickness) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The activation energy for oxidation of UO 2 by O 2 is reported to vary between 67 and 126 kJ mol À1 . These data refer to the dry oxidation of UO 2 by oxygen [29]. Recently a quantum chemical study revealed the important role of the presence of water on the surface of UO 2 in what concerns the oxidation of this material [30].…”
Section: Reactivity Of Different Oxidantsmentioning
confidence: 97%
“…The activation energy for oxidation of UO 2 by O 2 is reported to vary between 67 and 126 kJ mol À1 . These data refer to the dry oxidation of UO 2 by oxygen [29]. Recently a quantum chemical study revealed the important role of the presence of water on the surface of UO 2 in what concerns the oxidation of this material [30].…”
Section: Reactivity Of Different Oxidantsmentioning
confidence: 97%
“…In laboratory investigations of scaling phenomenon, reflectance FTIR can be used to follow the kinetics of scale growth, for example in the corrosion of uranium surfaces [30], but in situ monitoring of industrial processes has not been implemented. In laboratory investigations of scaling phenomenon, reflectance FTIR can be used to follow the kinetics of scale growth, for example in the corrosion of uranium surfaces [30], but in situ monitoring of industrial processes has not been implemented.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Although many researchers have empirically fit growth models to measured uranium oxidation behavior, none have modeled uranium oxidation using the basic physics of oxidation and known material properties. The dominant mechanism for oxidation of uranium at low temperatures and small oxide thicknesses is the motion of the ions through the generated electric field between the adsorbed oxygen ions at the surface and metal ions at the oxide–metal interface . Although a well‐established mechanism, theory‐driven models for the oxidation of uranium have not been formulated.…”
Section: Introductionmentioning
confidence: 99%
“…Although a well‐established mechanism, theory‐driven models for the oxidation of uranium have not been formulated. Until now only empirical oxidation models have been developed for uranium …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation